Learning Agility and Life Satisfaction as Predictors of Air Traffic Control Cadets’ Performance - Surtiningtyas, Sri Rahayu; Imam Sonhaji (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
The aviation industry in the Industry 4.0 era requires professionals with both technical proficiency and psychological adaptability. This study examines how learning agility and life satisfaction predict academic performance among first-year Air Traffic Control cadets at semi-military aviation colleges in Indonesia. Using a quantitative correlational design with a total population sample (N = 23), data were collected through the Learning Agility Scale for Students (α = 0.89) and the Satisfaction with Life Scale (α = 0.87). Multiple regression analysis showed that both variables explained 56% of the variance in academic performance (R² = 0.56, f² = 1.27). Result agility emerged as the strongest predictor, emphasizing goal orientation and perseverance in high-pressure learning environments. Life satisfaction also significantly influenced academic achievement, highlighting the role of well-being in sustaining motivation. The findings extend learning agility theory and suggest integrating resilience, soft skills, and well-being programs into aviation vocational curricula to enhance performance and readiness.